2021
DOI: 10.1016/j.ijhm.2020.102702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the COVID-19 pandemic: Evidence from the U.S. restaurant industry

Abstract: Highlights This study examines the relationship between various pre-pandemic firm characteristics and stock price reactions to COVID-19. This study employed GEE for analyses using STATA 15.1. Restaurant firms with larger size, more leverage, more cash flows, less ROA, and more internationalization are more resilient to stock declines. Dividend, franchising, institutional ownership, and managerial ownership did not show a significant mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
213
2
23

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 271 publications
(252 citation statements)
references
References 39 publications
14
213
2
23
Order By: Relevance
“…The event study method showed a negative influence of epidemics on restaurants’ stock returns of restaurants. Song et al (2020) explore the impact of COVID-19 on U.S. restaurant firms' stock returns. It is shown that firms with a larger size, more leverage, more cash flow, lower Return on Assets (ROA), and more internationalization are more resilient to the effects of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…The event study method showed a negative influence of epidemics on restaurants’ stock returns of restaurants. Song et al (2020) explore the impact of COVID-19 on U.S. restaurant firms' stock returns. It is shown that firms with a larger size, more leverage, more cash flow, lower Return on Assets (ROA), and more internationalization are more resilient to the effects of COVID-19.…”
Section: Literature Reviewmentioning
confidence: 99%
“…While many studies have examined the impact of epidemics or pandemics on tourism demand (among others, see Zeng, Carter, & De Lacy, 2005 ; Kuo, Chen, Tseng, Ju, & Huang, 2008 ; Chen, 2011 ; Rosselló, Santana-Gallego, & Awan, 2017 ; Karabulut, Bilgin, Demir, & Doker, 2020 ), the effect on the stock returns of tourism and hospitality companies is not yet well-explored. There are a few exceptions, such as Chen, Jang, and Kim (2007) and Chen (2011) on Severe Acute Respiratory Syndrome (SARS); Kim, Kim, Lee, and Tang (2020) on the effect of nine epidemics; and more recently, Song, Yeon, and Lee (2020) on COVID-19. In general, previous articles ( Chen et al, 2007 ; Kim et al, 2020 ) adopted an event study approach by choosing the outbreak of an epidemic as the event.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, social distancing is promoted in the interest of public health and is necessary. However, the measure has important effects on the economy, especially in the restaurant sector ( National Restaurant Association, 2020 , Song et al, 2021 ). The restaurant sector has expanded substantially over the past few years.…”
Section: Introductionmentioning
confidence: 99%